P(y) = exp(y*z)/SUM[y'=0..1](y'*z) = exp(y*z)/(exp(0*z)+exp(1*z)) = exp(y*z)/(1+exp(z)) 6.22
P(y) = Sigmoid((2*y-1)*z) 6.23
Hi guys! I'm a 30 years old software engineer living in Japan.
Recently, I'm studying machine learning and deep learning for my product and investment for myself.
I'm using text book from Raschka and Udacity deep le...
Hi,everyone , i am a Chinese student ,not a native English speaker , so you should cost much time to understand my english.
I am a senior student at the jiangsu University, maj...